Investasi Asing dalam Aspek Pembangunan Politik Menurut Pandangan Organski - Ramadhan Satriya Wicaksana (UNES Law Review, 2023)
The government is actively engaged in infrastructure development in various regions of Indonesia. This development is often viewed as a challenging project due to its high budget requirements. However, many consider the current development to be a long-term endeavor, the impacts of which will be felt in the next 10 to 15 years. The development being undertaken is seen as necessary to catch up with the previous era's development. In response to this, the government has implemented various investment schemes to expedite the development process so that its results can be swiftly experienced by the public. In connection with this, the author is interested in conducting research on this topic, linking the current infrastructure development in Indonesia with the theories proposed by Organski. This research will employ a juridical analysis and utilize literature review methods for data collection.